3-Hydroxy-4,7-megastigmadien-9-one, isolated from Ulva pertusa, attenuates TLR9-mediated inflammatory response by down-regulating mitogen-activated protein kinase and NF-κB pathways - Irshad Ali; Zahid Manzoor; Jung-Eun Koo; Jung-Eun Kim; Sang-Hee Byeon; Eun-Sook Yoo; Hee-Kyoung Kang; Jin-Won Hyun; Nam-Ho Lee; Young-Sang Koh (Taylor & Francis Group, 2017)
Context: Seaweeds are rich in bioactive compounds in the form of vitamins, phycobilins, polyphenols, carotenoids, phycocyanins and polysaccharides; many of these are known to have advantageous applications in human health. 3-Hydroxy-4,7-megastigmadien-9-one (comp) was isolated from Ulva pertusa (U. pertusa) Kjellman (Ulvaceae), which is a familiar edible green seaweed. Objective: This study evaluates the anti-inflammatory activity of comp in CpG DNA-stimulated bone marrow-derived dendritic cells (BMDCs). Materials and methods: For evaluating the effect of comp on cytokines production, BMDCs were treated with doses of comp (0, 0.5, 1, 2, 5, 10, 25 and 50 μM) for 1 h before stimulation with CpG DNA (1 μM). Cytokine production was measured by ELISA. Western blotting was conducted for evaluating effect of comp (50 μM) on MAPKs and NF-κB pathways. Luciferase reporter gene assay was conducted for effect of comp (0, 5, 10 and 25 μM) on transcriptional activity of AP-1 and NF-κB. Results: Comp exhibited strong inhibition of interleukin (IL)-12 p40, IL-6 and TNF-α cytokine production with IC50 values of 6.02 ± 0.35, 27.14 ± 0.73, and 7.56 ± 0.21 μM, respectively. It blocked MAPKs and NF-κB pathways by inhibiting the phosphorylation of ERK1/2, JNK1/2, p38 and IκBα. In addition, it strongly inhibited the transcriptional activity of AP-1 and NF-κB with IC50 values of 8.74 ± 0.31 and 12.08 ± 0.24 μM, respectively. Discussion and conclusion: Taken together, these data suggest that comp has a significant anti-inflammatory property and warrants further studies concerning the potential of comp for medicinal use.